ANALISIS PENGARUH RASIO PROFITABILITAS DAN RASIO SOLVABILITAS TERHADAP PERGERAKAN HARGA SAHAM SEKTOR AGRIBISNIS INDONESIA - Zulfikar Ardiansyah; Fathurrahman Fathurrahman; Baiq Dewi Lita Andiana (Nusantara Hasana Berdikari, 2022)
One sector that has an important role in the growth rate of the economy in Indonesia is the agribusiness sector. The Indonesia Stock Exchange has created an opportunity for agribusiness companies to go public. This research was conducted by direct observation at the Indonesia Stock Exchange (IDX) representative office of NTB. Multiple regression analysis method. The profitability variable (ROA) has a positive and significant effect on stock price movements. This can be seen from the results of the t-test which has a t-value of 0.471 with sig. t is 0.000 (p < 0.05). The solvency variable (DER) has a positive and significant effect on stock price movements. This can be seen from the results of the t-test which has a t-value of 1.126 with sig. t is 0.002 (p < 0.05). Profitability (ROA) and solvency (DER) variables simultaneously affect stock price movements. This is evidenced by the results of the F-test which produces an Fcount value of 23,635 with sig. of 0.000 (p < 0.05). The contribution of profitability (ROA) and solvency (DER) variables to stock price movements in the Indonesian agribusiness sector is 40.1 percent, while the remaining 59.9 percent is influenced by other variants outside the research model.